2016
DOI: 10.1016/j.jtusci.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspartame on the evaluation of electrophysiological responses in Wistar albino rats

Abstract: Aspartame is a non-nutritive sweetener that is used predominantly in various 'diet' and 'low-calorie' products, such as beverages, instant breakfasts, desserts, breath mints, sugar-free chewing gum, vitamins, and pharmaceuticals, consumed by millions of people who are attempting weight loss, young adults and diabetic persons. On a weight basis, the metabolism of aspartame generates approximately 50% phenylalanine, 40% aspartic acid and 10% methanol. The detailed mechanisms of the effects of aspartame on the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The present data indicate that the activity of SOD decreased significantly in the cardiomyocytes during the ASP treatment. The literature has shown that ASP chronic administration causes SOD activity to decline the liver and renal tissues [ 5 , 16 ], the spleen, thymus, lymph nodes, and bone marrow of rats [ 1 ]. The increased reactive oxygen species levels in the human heart are concerned with aortic valve stenosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data indicate that the activity of SOD decreased significantly in the cardiomyocytes during the ASP treatment. The literature has shown that ASP chronic administration causes SOD activity to decline the liver and renal tissues [ 5 , 16 ], the spleen, thymus, lymph nodes, and bone marrow of rats [ 1 ]. The increased reactive oxygen species levels in the human heart are concerned with aortic valve stenosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aspartame (ASP) is metabolized in the gastrointestinal tract and is absorbed by circulating blood as 50% phenylalanine, 40% aspartic acid, and 10% methanol, which causes the toxicity of ASP as described in detail previously [ 1 ]. The USA and Europe have recommended the acceptable daily intake of ASP as 50 and 40 mg/kg of body weight, respectively [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aspartame ingestion result in sympathetic dominance with loss of vagal tone and impaired cardiac function in rats [83,84]. Mostly Hypercortisolism is associated with central obesity, insulin resistance, dyslipidemia, and alterations in clotting and platelet function [85] (see Figure 3A and B).…”
Section: Hypercortisolism and Its Other Complicationsmentioning
confidence: 99%
“…Aspartame induces excess free radical production, in particular, reactive oxygen species (ROS) and reactive nitrogen species (RNS). These free radicals result in systemic oxidative stress [23] such as in blood cells [50,89,[115][116][117], brain cells [16,110,111,118,119], liver and kidney cells [20,22,120], heart cells [83,84] and immune organs [15,[121][122][123] (Figure 5). Systemic oxidative stress is associated with insulin resistance [124].…”
Section: Oxidative Stress To Insulin Resistancementioning
confidence: 99%
“…Recordings were analyzed by RMS EEG-24 Super sec version 1.1 and expressed in terms of amplitude (µv) and frequency (Hz). All experiments were performed at the same time of day (8:00:00-12:00 am) to eliminate variation due to circadian rhythms [29].…”
Section: Eegmentioning
confidence: 99%